Spatial segregation and realized niche shift during the parallel invasion of two olive subspecies in south‐eastern Australia. (29th May 2015) - Cornuault, Josselin; Khimoun, Aurélie; Cuneo, Peter; Besnard, Guillaume
Abstract Aim Greater understanding of the processes underlying biological invasions is required to determine and predict invasion risk. Two subspecies of olive (Olea europaea subsp. europaea and Olea europaea subsp. cuspidata) have been introduced into Australia from the Mediterranean Basin and southern Africa during the 19th century. Our aim was to determine to what extent the native environmental niches of these two olive subspecies explain the current spatial segregation of the subspecies in their non‐native range. We also assessed whether niche shifts had occurred in the non‐native range, and examined whether invasion was associated with increased or decreased occupancy of niche space in the non‐native range relative to the native range. Location South‐eastern Australia, Mediterranean Basin and southern Africa. Methods Ecological niche models (ENMs) were used to quantify the similarity of native and non‐native realized niches. Niche shifts were characterized by the relative contribution of niche expansion, stability and contraction based on the relative occupancy of environmental space by the native and non‐native populations. Results Native ENMs indicated that the spatial segregation of the two subspecies in their non‐native range was partly determined by differences in their native niches. However, we found that environmentally suitable niches were less occupied in the non‐native range relative to the native range, indicating that niche shifts had occurred through a contraction of the native niches after invasion, for both subspecies. Main conclusions The mapping of environmental factors associated with niche expansion, stability or contraction allowed us to identify areas of greater invasion risk. This study provides an example of successful invasions that are associated with niche shifts, illustrating that introduced plant species are sometimes readily able to establish in novel environments. In these situations the assumption of niche stasis during invasion, which is implicitly assumed by ENMs, may be unreasonable.